2013
DOI: 10.1016/j.econmod.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and volatility spillovers across commodity and stock markets: Linking energies, food, and gold

Abstract: This paper employs a VAR-GARCH model to investigate the return links and volatility transmission between the S&P 500 and commodity price indices for energy, food, gold and beverages over the turbulent period from 2000-2011. Understanding the price behavior of commodity prices and the volatility transmission mechanism between these markets and the stock exchanges are crucial for each participant, including governments, traders, portfolio managers, consumers, and producers. For return and volatility spillover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
196
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(230 citation statements)
references
References 43 publications
27
196
1
6
Order By: Relevance
“…Mensi et al (2013) have shown that volatility shocks to the S&P 500 can significantly affect the oil market; the results of their study are also confirmed for range volatility spillovers. Gao and Liu (2014) found that correlations between energy and grains indices and the S&P 500 increase in periods of volatility, which is also in line with the results above.…”
Section: Commodity: Financial Linkagessupporting
confidence: 65%
See 1 more Smart Citation
“…Mensi et al (2013) have shown that volatility shocks to the S&P 500 can significantly affect the oil market; the results of their study are also confirmed for range volatility spillovers. Gao and Liu (2014) found that correlations between energy and grains indices and the S&P 500 increase in periods of volatility, which is also in line with the results above.…”
Section: Commodity: Financial Linkagessupporting
confidence: 65%
“…But regime switches in the energy index appeared more closely related to equity volatility than those in the grains index. Mensi et al (2013) estimated bivariate VAR-GARCH models for pairs of indices for the period 2000-2011; the pairs consisted of the S&P 500 and the following indices: daily wheat, beverage, gold, crude oil, and Brent oil price. Past volatility and unexpected volatility shocks to the S&P 500 have significant effects on oil, gold, and beverage markets, but not on wheat markets.…”
Section: (Agricultural) Commodity-financial Market Linkagesmentioning
confidence: 99%
“…Park and Ratti [2008] use a VAR model. Many authors use the family of GARCH models, specifically bivariate GARCH [Cifarelli, Paladino 2010;Arouri, Lahiani, Nguyen 2011;Arouri 2011;Papież, Śmiech 2012], generalised VAR-GARCH [Arouri, Jouini, Nguyen 2012;Mensi et al 2013] and multivariate GARCH (Creti et al (2013) use dynamic conditional correlation (DCC) GARCH).…”
Section: Causality In Distribution Between European Stock Markets Andmentioning
confidence: 99%
“…Batten et al [11] found a significant impact of gold price volatility on the financial market returns. Mensi et al [16] studied the correlation and volatility transmission across commodities such as gold and crude oil, and equity market. The results of their study revealed that the changes in S&P500 affect gold and crude oil price volatility.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%
“…Baur and Mc Dermott [16] conducted a descriptive and econometric analysis of data from 1979 to 2009. Results of the study indicated that gold is mostly used as hedge against inflation and considered as safe haven for major European and US stock markets except Australia, Canada, Japan and emerging markets such as BRIC countries.…”
Section: Review Of Related Empirical Literaturementioning
confidence: 99%